Chants and rhymes to enhance the efl classroom’s speaking habits - Zuraidah Nasution; Imelda Darmayanti Manurung; Henilia (Institute of Computer Science (IOCS), 2023)
The paper discusses aspects of various activities to improve students’ vocabulary and skills, especially speaking habits. There is a need to encourage activities that help make learning English interesting. Songs are one of the activities that help students be active in class. The benefit of singing and reciting poetry is that the whole class can participate. Therefore, teachers can use these activities in the classroom to teach vocabulary. The goal is to help students understand new vocabulary and increase their awareness of using words in sentence structure and their grammatical patterns and combinations. The authors will also discuss how songs can reflect culture and increase students’ overall enjoyment of learning a second language. Using practical examples, we then use songs as language tasks. The goal is to explore how classic nursery rhymes can be adapted to a specific topic or part of the curriculum that a teacher wants to teach.